INFLUENCE OF ANTIHYPERTENSIVE DRUGS ON ARTERIAL STIFFNESS IN PATIENTS WITH ARTERIAL HYPERTENSION - N. V. Egorkina; V. M. Gorbunov; E. S. Abirova (Рациональная фармакотерапия в кардиологии, 2016)
Results of studies devoted to effects of various antihypertensive drugs on arterial stiffness in patients with arterial hypertension are presented. Advantages of angiotensin converting enzyme inhibitors and angiotensin receptor blockers are shown. Results of comparative studies on influence of combined therapy and monotherapy on arterial stiffness in hypertensive patients are also reviewed. Standard methods of arterial stiffness evaluation are estimated as mostly appropriate ones.